(untitled) (Innovative professional education, 2024)
The current state of public-private partnership in the field of vocational education is analyzed. The existing models of such partnership and mechanisms of interaction between the state and the private sector in the field of vocational education, which contain signs of public-private partnership, are determined. Modern trends in the development of public-private partnerships are identified. This makes it possible to establish their compliance with legal regulation, conceptual foundations, scientific achievements and best foreign practices.